Cycloolefin copolymer dielectrics for high temperature energy storage. (25th November 2022) - Qin, Hongmei; Liu, Man; Li, Ziwei; Fu, Yuheng; Song, Jinhui; Xie, Jian; Xiong, Chuanxi; Wang, Shan
Abstract: Cycloolefin copolymer (COC) could be a best promising commercial polymer dielectric for metallized film capacitors at elevated temperature according to the molecular structure, but the dielectric energy storage about COC remains a huge challenge due to the lack of processing strategies of its ultrathin films. Herein, we demonstrate that COC dielectric film of around 10 μm can be fabricated by solution casting followed by uniaxial stretching and steadily service at 140 °C. Excitedly, the charge-discharge efficiency ( η ) of COC film is up to 97.8 % at 600 MV/m at 25 °C, which is superior to the commercially available biaxially oriented polypropylene (BOPP). Remarkably, at 140 °C, COC film exhibits a maximum discharge energy density ( U e ) of 2.32 J/cm 3 and a η of 85.7 %, far outperforming the heat-resistant polyimide (PI) with a maximum U e of 1.00 J/cm 3 and a η of 24.1 %. Our work provides a novel strategy for the manufacture of ultrathin COC film and could promote the commercialization of high-temperature polymer capacitor films for the energy storage. Highlights: The stretching mechanism of COC film was verified and elaborated. COC exhibits ultrahigh charge-discharge efficiency and high breakdown field strength. The energy storage performance of COC is comparable to BOPP at RT and superior than PI at high temperature. The breakdown strength of COC was almost not affected after it was treated in acid, alkali and salt solution. Successful preparation of micron COC film by uniaxial stretching make it promising to be applied in film capacitors.